Integrative genetic and epigenetic control of skeletal muscle fiber traits in agricultural animals - Chang, Xiaolong; Ma, Junwu (Frontiers in Genetics, 2025)
Skeletal muscle fiber traits are fundamental to meat production and the meat quality of agricultural animals. The rich genetic resources and diverse phenotypic expression of muscle traits in agricultural animal species provide invaluable materials for investigating the genetic and molecular regulatory mechanisms underlying myofiber development and characteristics, optimizing breeding strategies, and developing models for human muscle-related diseases. This review presents an integrative perspective on the genetic and epigenetic regulation of skeletal muscle fiber development, incorporating evolutionary, genomic, epigenomic, and multi-omics insights. We focus on genetic architecture and causative or candidate genes for muscle fiber traits, as revealed by genome-wide association studies (GWAS) and selective sweep signatures, underscoring their adaptive significance and potential for selective breeding. The role of epigenetic mechanisms, such as DNA methylation, histone modifications, and non-coding RNAs, in linking genetic variation and phenotypic expression is also discussed. By synthesizing multi-omic data, we provide a comprehensive understanding of the molecular networks driving muscle fiber growth and differentiation. This review aims to consolidate current knowledge and offer actionable insights to advance research, breeding strategies, and applications in agricultural and biomedical fields.